The effects of inspiratory muscle strengthening on MIP and quality of life of elderly nursing home patients. (Los efectos del beneficio de la fuerza del músculo inspiratorio en la PIM y la calidad de la vida de los pacientes mayores de la clínica de reposo.) - Silvia Correa Bacelar; Estélio Henrique Martin Dantas; Rodrigo Gomes de Souzavale; Samária Ali Cader; Elirez Bezerra da Silva (Ramón Cantó Alcaraz, 2008)
Abstract The objective of this study was to compare the effects of inspiratory muscle strengthening on maximal inspiratory pressure (MIP) and on quality of life among elderly nursing home patients. The study population was divided in two groups: experimental group- EG (n=21, 76.48 2.12 years) and control group- CG (n=13, 75.69 2.26 years). The World Health Organization Quality of Life Group (WHOQOL-100) questionnaire was used to evaluate the quality of life of the subjects. A Manovacuometer (analogical, with an operational interval of -150 to +150 cmH2O; Critical Med/USA-2002) was used to evaluate MIP. The study protocol consisted of a gradual increase in workload (50%-100%); the sessions lasted 20 minutes and were composed of 7 series of strengthening (2 minutes each) with a 1-minute interval between the series, 3 times a week for 10 weeks. Variance analysis of multivariate repeated measurements demonstrated significant differences only for MIP between CG (32,69±17,03 cmH2O versus 23,08±10,71 cmH2O) and EG (31,67±11,11 cmH2O versus 55,24±23,26 cmH2O), and the latter was higher than the former (p= 0,00000). Therefore, we concluded that inspiratory muscle strengthening led to an increase in MIP that did not improve quality of life. However, further studies should be done in this population to validate a quality of life questionnaire specific for the elderly. Resumen El objetivo de este estudio era comparar los efectos del músculo inspiratorio que consolidaban en la presión inspiratoria máxima (PIM) y en la calidad de la vida entre pacientes mayores de la clínica de reposo. Dividieron a la población del estudio en dos grupos: grupo experimental EG. (n=21,76.48 2.12 años) y grupo de control CG (n=13, 75.69 2.26 años). La calidad de la Organización Mundial de la Salud del cuestionario del grupo de la vida(WHOQOL-100) fue utilizada para evaluar la calidad de la vida de los temas. Un Manovacuometer (analógico, con un intervalo operacional - de 150 a +150 cmH2O; Med/USA-2002 crítico) fue utilizado para evaluar la MIP.El protocolo del estudio consistió en un aumento gradual en la carga de trabajo (50%-100%); las sesiones duraron 20 minutos y fueron compuestas de 7 series de consolidación (2 minutos cada uno) con un 1 intervalo minucioso entre la serie, 3 veces a la semana por 10 semanas. El análisis de variación de medidas repetidas multivariate demostró diferencias significativas solamente para la MIPS entre CG (32,69±17,03 cmH2O contra 23,08±10,71 cmH2O) y EG. (31,67±11,11 cmH2O contra 55,24±23,26 cmH2O), y el último era más alto que el anterior (p= 0.00000). Por lo tanto, concluimos que el músculo inspiratorio que consolidaba condujo a un aumento en la MIPS que no mejoró la calidad de la vida. Sin embargo, otros estudios se deben hacer en esta población para validar una calidad del específico del cuestionario de la vida para los ancianos.